Plurilingualisme dalam Bahasa Suku Kayaan Medalaam Desa Datah Diaan Kecamatan Putussibau Utara Kabupaten Kapuas Hulu - Hadrianus Lung; Donatianus BSE Praptantya; Dahniar Th. Musa (Balale' : Jurnal Antropologi, 2022)
This study aimed to describe and analyze the languages of Kayaan Mendalaam Tribe. Umaa’ Aging, Umaa’ Suling, and Umaa’ Pagung are the three groups of language speakers. Plurilingualism is their experience speaking in more than one languages and using it according to their needs without actually mastering all the languages. This research used the ethnography method to provide the description of the research findings and the ethnography concept to analyze the languages. This study used qualitative descriptive approach. The tools of data collection were observation guidelines, interview guidelines, and documentation. The techniques of data collection were interviews, observation, and documentation. The study results found that the three groups of languages speakers have the same culture; however they are different in using the languages, especially in daily life, traditional ceremonies, and religious rituals. The languages differentiation is still lacking dan authors hopes that further research will complete this section.